Pharmaceutical markets and insurance worldwide - Dor, Avi, 1956- (Advances in health economics and health services research ;, 2010)
The fields of pharmaceutical economics and health economics/policy are reaching a point of convergence. This is due to both the widespread availability of pharmaceutical treatments, accompanied by broader insurance coverage, and the regulation of prescription drugs in both private and government plans. This book will bridge the gap. We will explore developments in both U.S. and International setting. The system of the U.S. is characterized by a mix of private and government insurance for prescription drugs with the expansion of Medicare Part D. Most other developed countries are characterized by social insurance with either the government as a single payer such as in Canada or Australia, or a national health service as in many other European countries.